KESULITAN MAHASISWA PPLK DALAM PERENCANAAN DAN PELAKSANAAN PEMBELAJARAN KURIKULUM 2013 (REVISI 2017) PERIODE JULI - DESEMBER 2017 JURUSAN TEKNIK SIPIL FT UNP - Gian Rahadian; Iskandar G Rani (CIVED, 2018)
This study aims to find out the percentage of the difficulties of pplk students in the planning and implementation of 2013 curriculum learning (Revised 2017) for the period July - December 2017 Department of Civil Engineering FT UNP. The research data was collected through a questionnaire distribution or questionnaire. The results showed that: (1) learning planning, (a) PPLK students experienced difficulty levels in the category of sufficient difficulty in preparing lesson plans with a percentage of 65%, (b) students experiencing difficulty in the category lacking difficulty in formulating competency achievement indicators with percentage 62 %, (c) PPLK students experience difficulty in the category of lack of difficulty in formulating learning objectives with a percentage of 63%, (d) PPLK students experience difficulty in the category of lack of difficulty in finding learning resources with a percentage of 61%, the level of difficulty in the category of lack of difficulty in explaining learning material with a percentage of 61%, (f) PPLK students experienced difficulty in the category of quite difficulty in determining learning strategies with a percentage of 72%. (2) the implementation of learning, (a) PPLK students experience difficulty in the category of sufficient difficulty in carrying out preliminary activities with a percentage of 71%, (b) PPLK students experience difficulty in the category of sufficient difficulty in carrying out core activities with a percentage of 71% ) PPLK students experienced difficulty in the category of quite difficulties in carrying out closing activities with a percentage of 65%.